Analysis of Student Learning Motivation for Project-Based Online Courses - Maharani, Putie; Afif, Nurullah Sururi; Zakharia, Anantha; Adianto, Harna (PT FORMOSA CENDEKIA GLOBAL, 2024)
This analysis aims to find out the extent to which motivation affects students in project-based online courses. Where this project-based learning was first applied to religious courses, civic education and other courses at Bina Sarana Informatics University. Data collection was carried out by distributing questionnaires online to 100 students using the respondent achievement level analysis (TCR) research method. With the results, for online learning, 81.6% of students with the very good category can follow. For project-based learning, 78.4 – 79.8 percent are still in the good category, which means that there is still a need for improvement so that students can receive optimally.